Tax Avoidance Dynamics in Fast-Moving Consumer Goods Companies: The Moderating Role of Firm Size - Nane Kurnia; Sasa S. Suratman; Aditya Jasa Anggeraja; Ella Herlianti (Al-Qalam Institue, 2026)
This study aims to examine the effects of profitability, leverage, and sales growth on tax avoidance, as well as to investigate the moderating role of firm size in these relationships. The study employs a quantitative research approach using secondary data obtained from annual financial reports. The sample was selected through purposive sampling based on predetermined criteria. Tax avoidance serves as the dependent variable, while profitability, leverage, and sales growth function as independent variables. Firm size is incorporated as a moderating variable. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA) with EViews 13. The findings indicate that profitability does not have a significant effect on tax avoidance. In contrast, leverage and sales growth significantly influence tax avoidance practices. Furthermore, firm size does not moderate the relationship between profitability and tax avoidance, but it significantly moderates the effects of leverage and sales growth on tax avoidance. These results suggest that tax avoidance behavior is more strongly influenced by financing structure, business growth, and organizational scale than by profitability. The study contributes to the tax accounting literature and provides practical implications for strengthening financial governance, tax compliance awareness, and business ethics education in higher education.